Influence of Topiramate on the Synaptic Endings of the Temporal Lobe Neocortex in an Experimental Model of Hyperthermia-Induced Seizures: An Ultrastructural Study - Piotr Sobaniec (MDPI AG, 2021)
The objective of this pioneering study was to assess potentially neuroprotective properties of topiramate (TPM), a broad spectrum and newer-generation antiepileptic used against damage to synaptic endings of the temporal lobe neocortex in experimental hyperthermia-induced seizures (HS). TPM (80 mg/kg b.m.) was administered in young male Wistar rats with an intragastric tube before and immediately after HS. Specimens (1 mm3) collected from the neocortex, fixed via transcardial perfusion with paraformaldehyde and glutaraldehyde solution, were routinely processed for transmission-electron microscopic study, i.e., for descriptive and morphometric analysis. The ultrastructure of neocortical neuropil components affected by hyperthermic stress showed distinct swelling of pre and post-synaptic axodendritic and axospinal endings, including total disintegration. Mitochondria were markedly damaged in synaptic structures. Axoplasm of presynaptic boutons contained a decreased number of synaptic vesicles. Synaptic junctions showed active zone-shortening. Preventive administration of TPM before HS induction demonstrated neuroprotective effects against synaptic damage in approximately 1/4 of these structures. Interestingly, beneficial effects on synapsis morphology were more common in perivascular zones close to well-preserved capillaries. They were demonstrated by smaller swelling of both presynaptic and postsynaptic parts, well-preserved mitochondria, an increased number and regular distribution of synaptic vesicles within axoplasm, and a significantly increased synaptic active zones. However, topiramate used directly after HS was ineffective in the prevention of hyperthermia-evoked synaptic injury. Our findings support the hypothesis that topiramate applied before HS can protect some neocortical synapses via the vascular factor by enhancing blood–brain barrier components and improving the blood supply of gray matter in the temporal lobe, which may be significant in febrile seizure-prevention in children.